A PILOT EXPLORATION OF THE RELATIONSHIP BETWEEN TEMPERAMENT AND PSYCHOPATHOLOGY IN 12–18 YEAR-OLD CHILDREN BORN AT EXTREMELY LOW BIRTH WEIGHT - Borrageiro, Dannita; Govender, Catherine (New Voices in Psychology, 2017)
This pilot study was aimed at exploring the temperament and psychopathology distribution amongst adolescents born at extremely low birth weight (ELBW), i.e. < 1000g. ELBW adolescents (N = 15) completed the Revised Cheek and Buss Scale and Mini International Neuropsychiatric Interview 5.0.0 (M.I.N.I.), while their legal guardians completed a biographical questionnaire. The median age of the sample was 13 SD = 2.526 years (60% male) and all participants spoke English. The results suggest that being born at ELBW is associated with shyness in adolescence. Anxieties, mood and hyperactivity symptoms were prevalent. Planning of interventions for ELBW individuals should therefore include strategies to prevent or mitigate the effects of these factors in adolescence.